Removal of phosphate from aqueous solution by thermally treated natural palygorskite - Gan, Fangqun; Zhou, Jianmin; Wang, Huoyan; Du, Changwen; Chen, Xiaoqin (Water research (Oxford), 2009)
The potential of activated palygorskite was assessed for sorption of phosphate from aqueous solution. The natural palygorskite used was treated by thermal activation over 100–1000 °C for 2 h. The thermal activation increased the phosphate sorption capacity and the highest phosphate sorption capacity occurred at 700 °C. H700 (palygorskite heated at 700 °C) showed higher sorption rate than natural palygorskite (NPAL), and the removal was favorable in acidic media. The sorption data were described using Freundlich isotherm equation over the concentration range (5–1000 mg/L) (25 °C). Calcium bound phosphorus was the main fraction of the adsorbed phosphorus, about 98.0% in NPAL and 58.2% in H700, but the extractive Ca–P species varied greatly, Ca 2–P was 87.7% in NPAL and 3.0% in H700, Ca 8–P was 10.1% in NPAL and 54.5% in H700, and metal bound phosphorus was less than 2% in NPAL but more than 41.4% in H700, respectively. The dependence of the phosphate sorption capacity in the heating samples on thermal activation appears to be related to major changes in the crystal structure of palygorskite, and more calcium, iron and aluminum were released from the crystal matrix at 700 °C, which promoted phosphorus sorption.